Patently peculiar: Patents and innovation in the United Kingdom of the Netherlands - Homer Wagenaar; Christopher L. Colvin (Queen's University Centre for Economic History (QUCEH), 2025)
We examine the accessibility and functioning of the patent system in the United Kingdom of the Netherlands, a state that existed between 1815 and 1830. The country's patent law combined an examination process with significant government discretion over a patent's duration and cost. Using our hand-collected database of all patent applications-granted, withdrawn, and rejected-we analyse the determinants of success, and the conditions imposed on applicants by the system's administrators. We find that discretion optimised patent terms rather than causing bias. The system was accessible despite high fees. Our analysis suggests that social class, skills, and market orientation drove the demand for patents. Our research contributes to understanding the history of European patent institutions by adding high-quality patent data for the second economy in the world to experience an Industrial Revolution.
Keywords: L51; N44; N74; O31; O34; 330; patents; innovation; industrialisation; discretion; Low Countries